n-scroll chaos generators: a simple circuitmodel - Yalçin, M.E.; Özoğuz, S.; Suykens, J.A.K.; Vandewalle, J. (Institution of Engineering and Technology (IET), 2001)
n-scroll attractors which are generated from a generalised and simple circuit model are presented. The nonlinear characteristics can be systematically designed by adding comparators. A 5-scroll attractor circuit realisation is shown, which has been experimentally verified using current feedback opamps.